Cracks in the Glass Ceiling: Gender and Promotion in the Economics Profession - McDowell, John M; Singell, Larry D; Ziliak, James P (American Economic Review, 1999)
Cracks in the Glass Ceiling: Gender and Promotion in the Economics Profession by John M. McDowell, Larry D. Singell and James P. Ziliak. Published in volume 89, issue 2, pages 392-396 of American Economic Review, May 1999